1980
DOI: 10.2307/1937405
|View full text |Cite
|
Sign up to set email alerts
|

Kelp Beds and Sea Otters: An Experimental Approach

Abstract: In Torch Bay, Alaska, USA, sea urchins structure shallow subtidal communities by consuming most macroscopic algae. Experimental removal of urchins leads to the development, within 1 yr, of a kelp association of high biomass and diversity. In the 2nd yr, however, these attributes decrease as a single kelp species, Laminaria groenlandica, becomes dominant. Additional field experiments confirm the competitive superiority of this kelp. These manipulations lead to predictions regarding the ecological role of sea ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
157
3
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(171 citation statements)
references
References 18 publications
(23 reference statements)
8
157
3
3
Order By: Relevance
“…These forests form the foundation for many ecological and physical processes, providing numerous ecosystem services (Lünning, 1990;Steneck et al, 2002). Kelp acts as both substratum for many sessile animals and algae and as habitat for mobile organisms living in and feeding directly on the kelp or their associated species (Duggins, 1980;Christie et al, 2009). A decline in habitat-forming subtidal kelp unsurprisingly results in major changes in near shore community composition (Schiel et al, 2004;Wernberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These forests form the foundation for many ecological and physical processes, providing numerous ecosystem services (Lünning, 1990;Steneck et al, 2002). Kelp acts as both substratum for many sessile animals and algae and as habitat for mobile organisms living in and feeding directly on the kelp or their associated species (Duggins, 1980;Christie et al, 2009). A decline in habitat-forming subtidal kelp unsurprisingly results in major changes in near shore community composition (Schiel et al, 2004;Wernberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Abundance, size structure, and feeding behavior of sea urchins may be influenced by predation (Duggins 1980;Tegner and Dayton 1981;McClanahan and Shafir 1990;Sala and Zabala 1996;Scheibling 1996;Guidetti et al 2003), which stresses the potentially great functional importance of consumers of echinoids in the control of sea urchin populations and, furthermore, the structure of entire communities associated with rocky substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these general features of their ecology sea urchins have been conspicuous in studies that seek to isolate and explain the processes that structure marine communities. These studies have shown that sea urchins can have a profound influence on the structure of benthic communities (Ogden et al 1973, Estes & Palmisano 1974, Duggins 1980, Andrew & Choat 1982, Dean et al 1984, Dayton 1985; see Lawrence 1975, Lawrence & Sammarco 1982.…”
mentioning
confidence: 99%